O casamento-um rito de passagem. Seus vestígios na região transmontana (Bragança) - Afonso, Belarmino (Trabalhos de Antropologia e Etnologia, 2020)
There are privileged sources of research which supply the investigator with indispensable information for the knowledge of a particular community. The transitory rites, especially those concerning marriages, strongly unveil the way cif feeling of a people. Once we learn about marriages, it is possible to determine the good or bad relationship of the married couples and their families, as well as their social and economical status. 'ln the case of archaic communities, economically dependent from farming/ /pastoral activities, supernatural-believes constitute the main component to condition the behaviour of the youths approaching marriage. That is, superstition makes it easier, or more difficult, for the young boys and girls to get together. Social sanctions imposed by the community at Bragança such as the «paga- vinho» (1), and the «chocalhada» (2) are curious aspects of the people, still in use in some villages. The «loas»' (3), as well as their proverbs, clearly reveal the poetic and philosophical sense always present in the most important moments of their lives. This work is the result of a research done on the subject within the district of Bragança and it is hoped that it contributes to the social! cultural study of the population of this region, which, at present, is going through times of great change and in danger of losing their identity and traditions.